LRRK2 pathobiology in Parkinson's disease – virtual inclusion. (22nd February 2016) - Martin, Ian; Kim, Jungwoo Wren; Dawson, Valina L.; Dawson, Ted M.
Abstract: A common cause of Parkinson disease are missense mutations in the leucine‐rich repeat kinase 2 (LRRK2) catalytic Roc‐COR domain, leading to a decrease in GTPase activity; and its kinase domain, leading to an increase in kinase activity and subsequent LRRK2 toxicity. Targeting LRRK2 with selective, brain‐permeable kinase inhibitors is a promising approach to reduce toxicity, and thus is a major goal of clinical development. Understanding the specific signaling cascades triggered by LRRK2 mutations will be key to this aim. This article is part of a special issue on Parkinson disease . Abstract : This article is part of a special issue on Parkinson disease .